Non-linear Relationship of Maternal Age With Risk of Spontaneous Abortion: A Case-Control Study in the China Birth Cohort - Zhang, Man; Yang, Bo-Yi; Sun, Yongqing; Qian, Zhengmin; Xaverius, Pamela K.; Aaron, Hannah E.; Zhao, Xiaoting; Zhang, Zheng; Liu, Ruixia; Dong, Guang-Hui; Yin, Chenghong; Yue, Wentao (Frontiers in Public Health, 2022)
Background Spontaneous abortion is one of the prevalent adverse reproductive outcomes, which seriously threatens maternal health around the world. Objective The current study is aimed to evaluate the association between maternal age and risk for spontaneous abortion among pregnant women in China. Methods This was a case-control study based on the China Birth Cohort, we compared 338 cases ending in spontaneous abortion with 1,352 controls resulting in normal live births. The main exposure indicator and outcome indicator were maternal age and spontaneous abortion, respectively. We used both a generalized additive model and a two-piece-wise linear model to determine the association. We further performed stratified analyses to test the robustness of the association between maternal age and spontaneous abortion in different subgroups. Results We observed a J-shaped relationship between maternal age and spontaneous abortion risk, after adjusting for multiple covariates. Further, we found that the optimal threshold age was 29.68 years old. The adjusted odds ratio (95% confidence interval) of spontaneous abortion per 1 year increase in maternal age were 0.97 (0.90–1.06) on the left side of the turning point and 1.25 (1.28–1.31) on the right side. Additionally, none of the covariates studied modified the association between maternal age and spontaneous abortion (P > 0.05). Conclusions Advanced maternal age (>30 years old) was significantly associated with increased prevalence of spontaneous abortion, supporting a J-shaped association between maternal age and spontaneous abortion.